Factors for Successful Science Learning in a Flexible Mode amid Covid-19 Educational Disruption: Students’ Assessment - Saldivar, John Ray V.; Fontila, May Lheena; Rogayan, Danilo V.; Deymos, Marc R.; Monje, Stephen John R. (Jurnal Penelitian dan Pembelajaran IPA, 2022)
Due to the educational disruption caused by the COVID-19 pandemic, educational institutions resorted to flexible learning modalities to continue the education of students and avoid learning losses. This descriptive online survey assessed different factors for successful science learning in a flexible mode utilized during the current learning setup. A total of 50 teacher education students specializing in science from the two campuses of a state university in Zambales, Philippines, responded to the researcher-crafted survey questionnaire (α=0.971). Results of the study showed that most of the respondents are using the online asynchronous learning modality. Almost all of them are using smartphones for their flexible learning. The college students strongly agree that instructor characteristics is a primary factor for successful science learning in a flexible mode, followed by internet accessibility, administrative support, course content and design, technical support, learner characteristics, and social support. Significant differences were noted in the factors for successful science learning in a flexible mode when grouped according to the learning modality used. Furthermore, positive significant moderate to high correlations were observed among factors for successful science learning in a flexible mode. The study suggests that schools may provide instructors with training and seminars about flexible education to further enhance their content knowledge and pedagogy in science, specifically in this educational disruption. Additionally, the university may craft programs and policies that address students' concerns in the current learning setup to avoid learning losses. These programs and policies could make the current learning modality more effective, efficient, and responsive to the students' needs, and more conducive for both faculty and students. Future researchers could conduct a further study to evaluate college students' experiences in flexible learning modalities in university for the past semesters.